Supervisi Ketua Program Studi dalam Peningkatan Moral Mahasiswa - Muhammad Nur Hakim (Universitas Pesantren Tinggi Darul 'Ulum, 2020)
Responding to the development of the new era is higher, so that the Indonesian state does not get left behind by responding to these advancements. And the most dominant thing related is education that leads to human development processes. In this context, it really needs supervision and evaluation of policies and the implementation of all the power in have, specifically this research was conducted to describe how educational organizations are monitored by KH Abdul Chalim Islamic Boarding School which has a santri and pesantren base morals based on the policies of the head of the study program and some strategies that have technically inspired moral improvement through supervision.